LITERATURE REVIEW: TERAPI PIJAT PADA BAYI PREMATURE BERAT BADAN LAHIR RENDAH DAPAT MEMBANTU MENAIKKAN BERAT BADAN BAYI - Munir, Zainal; Winarsih, Winarsih (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
Low birth weight (LBW) is an indirect cause of neonatal death. LBW accounts for up to 60% to 80% of all neonatal deaths. The number of low birth weight babies in developed countries consists of two-thirds of premature babies and the rest of them are old enough but experience growth retardation in the womb. Low birth weight babies consist of premature babies and old enough babies who experience growth retardation in the womb. Premature babies or babies whose birth weight is less than 2500 g. Methods: The research method we use here is a literature review using an electronic database through national and international journals such as Pubmed, Science Direx, Google scholar. Result: there is a difference before and after being given baby massage therapy on the baby's weight, so that baby massage therapy can be applied to premature babies to optimize newborn weight. Conclusion: massage therapy in premature babies with low birth weight can help increase body weight. babies, improve the brain development of premature babies and the development of nerves in infants.